Cover Image. (23rd October 2020) - Yoshikawa, Kenji; Úbeda, Jose; Masías, Pablo; Pari, Walter; Apaza, Fredy; Vasquez, Pool; Ccallata, Beto; Concha, Ronald; Luna, Gonzalo; Iparraguirre, Joshua; Ramos, Isabel; De la Cruz, Gustavo; et al.
Abstract : The cover image is based on the Research Article Current thermal state of permafrost in the southern Peruvian Andes and potential impact from El Niño–Southern Oscillation (ENSO) by Kenji Yoshikawa et al., https://doi.org/10.1002/ppp.2064 .